AI-Based Teacher Assistants in Indonesian Public Schools: A Case Study of Teachy - Uswatun Hasanah; Dzulfikri; Junaidi Mistar (Universitas Islam Negeri Palopo, 2025)
This study examines how Teachy, an AI-based educational platform, supports teachers’ work in Indonesian public schools. Conducted in Lumajang Regency, East Java, a rural region with limited technological resources, the qualitative case study involved four teachers from junior and senior high schools using Teachy for at least one academic semester. Data collected during the even semester of the 2024/2025 academic year, through interviews, observations, and document analysis, were analysed thematically. Eight themes emerged, including workload assisting, cognitive and pedagogical shifts, emotional responses, leadership support, collaboration, and sustainability challenges. Teachers reported saving 2–4 hours weekly on planning and assessment tasks through automation features. However, barriers such as unstable internet access and insufficient digital literacy limited optimal use. One teacher noted that poor connectivity caused frequent interruptions during digital lesson delivery. The findings demonstrate that AI tools can enhance efficiency and instructional quality when embedded within supportive institutional environments. This study offers one of the few empirical examinations of AI adoption in rural Indonesian schools, contributing new insights to global discussions on AI integration in low-resource settings.